2022
DOI: 10.1111/ajt.16980
|View full text |Cite
|
Sign up to set email alerts
|

OPTN/SRTR 2020 Annual Data Report: VCA

Abstract: The first vascularized composite allograft (VCA) transplant in the United States was performed in 1998 in a 40‐year‐old man who received a laryn‐geal transplant after experiencing severe trauma to the throat 20 years before. The following VCA was a hand transplant in 1999 in a 37‐year‐old man who lost his left hand 13 years before. Since then, the field of VCA transplantation has made significant strides. On July 3, 2014, the Or gan Procurement and Transplantation Network (OPTN)/United Network for Organ Sharin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Evaluations of perceived gender and race in lymphedema surgeon faculty demonstrated that greater proportions of lymphedema surgeons were women and races other than Caucasian when compared with studies assessing the perceived demographics of the plastic surgery specialty collectively. 17 28 Faculty perceived as female or a race underrepresented in plastic surgery had significantly less research productivity than their counterparts, though this may be the result of these populations having significantly more assistant professor titles and significantly fewer years of experience. Both high research productivity and diversity of faculty contribute to the overall ranking, reputation, and desirability of a plastic surgery residency program, as these are elements reported to be influential to plastic surgery applicants when going through the program selection process.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluations of perceived gender and race in lymphedema surgeon faculty demonstrated that greater proportions of lymphedema surgeons were women and races other than Caucasian when compared with studies assessing the perceived demographics of the plastic surgery specialty collectively. 17 28 Faculty perceived as female or a race underrepresented in plastic surgery had significantly less research productivity than their counterparts, though this may be the result of these populations having significantly more assistant professor titles and significantly fewer years of experience. Both high research productivity and diversity of faculty contribute to the overall ranking, reputation, and desirability of a plastic surgery residency program, as these are elements reported to be influential to plastic surgery applicants when going through the program selection process.…”
Section: Discussionmentioning
confidence: 99%
“…After the first described hand transplantation attempt in 1964 (1), it took 34 years for VCA to become a clinical reality thanks to the advent of potent immunosuppressive therapies like calcineurin inhibitors (CNI) (2). Since then, the field has expanded greatly, with over 170 VCAs performed worldwide, including face, hand, uterus, and abdominal wall transplantations (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%